Should environmental taxes be imposed on agriculture? Analysis from the welfare perspective - Zhang, Zheng; Wu, Guangpu; Guo, Ying; Zhang, Xiaran (Frontiers in Sustainable Food Systems, 2023)
Environmental taxation is an essential regulatory tool for governments seeking to optimize agricultural production, enhance the environment, and guarantee food safety. Concerns exist, however, regarding the imposition of environmental taxes on agriculture, as this could be detrimental to the interests of agricultural producers and consumers. To better comprehend the effects of agricultural environmental taxes on production decisions, the environment, the economy, and society, this paper constructs a mathematical model and analyzes optimal outcomes from a welfare perspective. The study examines the structure of consumer groups, classifying them as either green or non-green. Several intriguing conclusions are drawn. First, when both consumer groups coexist on the market, imposing environmental taxes on non-green agricultural producers does not always result in a reduction in social welfare. Within a specific tax range, it is possible to accomplish a tripling of social welfare, agricultural producer welfare, and environmental benefits. Second, as the tax rate rises, the environment progressively improves while consumer surplus diminishes. Within a particular tax range, producer surplus and social welfare both increase. Thirdly, as the proportion of green consumers in the market and ordinary consumers' awareness of green agricultural commodities increases, the positive impact of taxation on the environment decreases, while its positive impact on producer surplus and consumer surplus increases. Taxation can also have a positive effect on the general social welfare under certain conditions. This paper examines the viability of environmental taxation in agriculture from the perspective of social welfare, providing governments with valuable insights for regulating agricultural production and environmental management. In addition, policymakers can use the findings as a guide for formulating effective measures to promote sustainable agriculture and environmental stewardship.